Critical Growth Processes for the Midfacial Morphogenesis in the Early Prenatal Period. (September 2019) - Katsube, Motoki; Yamada, Shigehito; Yamaguchi, Yutaka; Takakuwa, Tetsuya; Yamamoto, Akira; Imai, Hirohiko; Saito, Atsushi; Shimizu, Akinobu; Suzuki, Shigehiko
Background: Congenital midfacial hypoplasia often requires intensive treatments and is a typical condition for the Binder phenotype and syndromic craniosynostosis. The growth trait of the midfacial skeleton during the early fetal period has been assumed to be critical for such an anomaly. However, previous embryological studies using 2-dimensional analyses and specimens during the late fetal period have not been sufficient to reveal it. Objective: To understand the morphogenesis of the midfacial skeleton in the early fetal period via 3-dimensional quantification of the growth trait and investigation of the developmental association between the growth centers and midface. Methods: Magnetic resonance images were obtained from 60 human fetuses during the early fetal period. Three-dimensional shape changes in the craniofacial skeleton along growth were quantified and visualized using geometric morphometrics. Subsequently, the degree of development was computed. Furthermore, the developmental association between the growth centers and the midfacial skeleton was statistically investigated and visualized. Results: The zygoma expanded drastically in the anterolateral dimension, and the lateral part of the maxilla developed forward until approximately 13 weeks of gestation. The growth centers such as the nasal septum and anterior portion of the sphenoid were highly associated with the forward growth of the midfacial skeleton (RV = 0.589; P < .001). Conclusions: The development of the midface, especially of the zygoma, before 13 weeks of gestation played an essential role in the midfacial development. Moreover, the growth centers had a strong association with midfacial forward growth before birth.